Natural and commercial antimicrobial agents that inhibit the growth of Listeria monocytogenes strains (Scientia Agropecuaria, 2022)
Vinegar products have gained popularity as an all-natural antimicrobial agent in recent years. In the present study, the antimicrobial susceptibility of 29 Listeria monocytogenes strains isolated from ready-to-eat foods was detected against natural and commercial antimicrobial agents, vinegar produced from different raw materials, lemon juice, sodium bicarbonate, and hydrogen peroxide, by using the disc diffusion method. Different concentrations of antimicrobial agents were tested against varying cell densities of the L. monocytogenes strain (105, 106, and 107 CFU/mL). The inhibition zone diameter was measured to evaluate the antimicrobial effects of antimicrobial agents on L. monocytogenes strains. The inhibition zone diameters of L. monocytogenes strains were 6.0–8.8 mm and 6.0–11.3 mm against traditional and commercial vinegar types, respectively. The commercial vinegar types showed higher antimicrobial efficacy than the conventional ones. The inhibition zone diameters of L. monocytogenes strains against carbonate, lemon juice, and hydrogen peroxide were 6.0, 6.0–9.0, and 33.9–51.9 mm, respectively. The antimicrobial efficacy of hydrogen peroxide was the highest among the tested antimicrobial agents. This study showed that vinegar products have potential to be utilized as natural antimicrobials on food-borne pathogens like L. monocytogenes.